Hybrid coating of titanium alloys via liquid additive manufacturing method: a review of recent advances - Naping, Rosmia; Maleque, Md. Abdul; Sarifuddin, Norshahida; Hassan, Masjuki; Bello, Kamilu Adeyemi (2023)
This paper reviews the recent advancement of hybrid coating on titanium alloys via liquid additive manufacturing method through a literature search to identify major trends and developments in this field. Hybrid coatings created a new class of coatings with superior and customized properties, revolutionizing high-performance applications in industries such as automotive, aerospace, marine, and construction. The review covers hybrid coating fundamentals, metallic substrate selection, various coating methods, and coating characterization. Hybrid coatings and their advantages over single-material coatings are also reviewed. The benefits and drawbacks of surface coating processes of liquid additive manufacturing, sol-gel deposition, laser beam, thermal spraying, and micro-arc oxidation are analyzed. Based on the literature review, it can be found that TIG torch LAM technology is cheaper, sustainable, allows hybrid coating development by precisely controlling coating thickness and composition, and also exhibited better morphology and hardness properties in titanium alloys. Finally, the prospect of future trends of hybrid coating is highlighted. Therefore, it is hoped that the shift of highly expensive laser beam liquid and sol-gel deposition methods to the LAM for sustainable hybrid coating would be greener, environmentally friendly, and major significant to this type of research. The case study that has been presented in this paper for the hybrid coating on commercial purity titanium theory showed that hybrid coating enhances hardness value by 3-4 times and developed new microstructure.